Effect of water on the fluorine and chlorine partitioning behavior between olivine and silicate melt - Joachim, Bastian; Ludwig, Thomas (Contributions to mineralogy and petrology, 2017)
Halogens show a range from moderate (F) to highly (Cl, Br, I) volatile and incompatible behavior, which makes them excellent tracers for volatile transport processes in the Earth’s mantle. Experimentally determined fluorine and chlorine partitioning data between mantle minerals and silicate melt enable us to estimate Mid Ocean Ridge Basalt (MORB) and Ocean Island Basalt (OIB) source region concentrations for these elements. This study investigates the effect of varying small amounts of water on the fluorine and chlorine partitioning behavior at 1280 °C and 0.3 GPa between olivine and silicate melt in the Fe-free CMAS+F-Cl-Br-I-H2O model system. Results show that, within the uncertainty of the analyses, water has no effect on the chlorine partitioning behavior for bulk water contents ranging from 0.03 (2) wt% H2O (DCl ol/melt = 1.6 ± 0.9 × 10−4) to 0.33 (6) wt% H2O (DCl ol/melt = 2.2 ± 1.1 × 10−4). Consequently, with the effect of pressure being negligible in the uppermost mantle (Joachim et al. Chem Geol 416:65-78, 2015), temperature is the only parameter that needs to be considered for the determination of chlorine partition coefficients between olivine and melt at least in the simplified iron-free CMAS+F-Cl-Br-I-H2O system. In contrast, the fluorine partition coefficient increases linearly in this range and may be described at 1280 °C and 0.3 GPa with (R 2 = 0.99): Dol/meltF = 3.6±0.4 × 10−3 × XH2O(wt % ) + 6 ± 0.4×10−4DFol/melt = 3.6±0.4 × 10−3 × XH2O(wt % ) + 6 ± 0.4×10−4D_{F}^{\text{ol/melt}}\ =\ 3.6± 0.4\ × \ {{10}^{-3}}\ × \ {X_{{{\text{H}}_{\text{2}}}\text{O}}}\left( \text{wt }\!\!%\!\!\text{ } \right)\ +\ 6\ ± \ 0.4× \,{{10}^{-4}}. The observed fluorine partitioning behavior supports the theory suggested by Crépisson et al. (Earth Planet Sci Lett 390:287-295, 2014) that fluorine and water are incorporated as clumped OH/F defects in the olivine structure. Results of this study further suggest that fluorine concentration estimates in OIB source regions are at least 10% lower than previously expected (Joachim et al. Chem Geol 416:65-78, 2015), implying that consideration of the effect of water on the fluorine partitioning behavior between Earth’s mantle minerals and silicate melt is vital for a correct estimation of fluorine abundances in OIB source regions. Estimates for MORB source fluorine concentrations as well as chlorine abundances in both mantle source regions are within uncertainty not affected by the presence of water.